Cytolytic Properties and Genome Analysis of Rigvir® Oncolytic Virotherapy Virus and Other Echovirus 7 Isolates - Hietanen Eero; Koivu Marika A; Susi Petri (MDPI, 2022)
Rigvir® is a cell-adapted, oncolytic virotherapy enterovirus, which derives from an echovirus 7 (E7) isolate. While it is claimed that Rigvir® causes cytolytic infection in several cancer cell lines, there is little molecular evidence for its oncolytic and oncotropic potential. Previously, we genome-sequenced Rigvir® and five echovirus 7 isolates, and those sequences are further analyzed in this paper. A phylogenetic analysis of the full-length data suggested that Rigvir® was most distant from the other E7 isolates used in this study, placing Rigvir® in its own clade at the root of the phylogeny. Rigvir® contained nine unique mutations in the viral capsid proteins VP1-VP4 across the whole data set, with a structural analysis showing six of the mutations concerning residues with surface exposure on the cytoplasmic side of the viral capsid. One of these mutations, E/Q/N162G, was located in the region that forms the contact interface between decay-accelerating factor (DAF) and E7. Rigvir® and five other isolates were also subjected to cell infectivity assays performed on eight different cell lines. The used cell lines contained both cancer and non-cancer cell lines for observing Rigvir®’s claimed properties of being both oncolytic and oncotropic. Infectivity assays showed that Rigvir® had no discernable difference in the viruses’ oncolytic effect when compared to the Wallace prototype or the four other E7 isolates. Rigvir® was also seen infecting non-cancer cell lines, bringing its claimed effect of being oncotropic into question. Thus, we conclude that Rigvir®’s claim of being an effective treatment against multiple different cancers is not warranted under the evidence presented here. Bioinformatic analyses do not reveal a clear mechanism that could elucidate Rigvir®’s function at a molecular level, and cell infectivity tests do not show a discernable difference in either the oncolytic or oncotropic effect between Rigvir® and other clinical E7 isolates used in the study.